Gugatan Harta Waris Terhadap Anak Angkat Analisis Yuridis Terhadap Putusan PA Situbondo No. 0371/Pdt.G/2017/PA.Sit - Muhammad Ibnul Hasan; Rosyidatul Khoiriyah (AL-ISTINBATH : Jurnal Hukum Islam, 2019)
This study aims to determine the rights and status of adopted children to the inheritance of their parents according to Islamic law and to determine the decision of the Religious Court regarding the lawsuit against inheritance which is controlled by adopted children. This type of research is a normative legal research that studies secondary data with descriptive-analysis research specifications. Inheritance is often the reason for a split in the family, so there is a law governing who is entitled and what level is entitled to each family member. But one problem that often arises is the mastery of inheritance by adopted children. In Islamic law, the status of adopted children cannot be equalized with biological children because adopted children are not included in inherited family relationships. The results of this study are that adopted children are not included as heirs so as to obtain the compulsory will of 1/3 of the inheritance of their adopted parents according to the Jurisprudence of the Religious Court and in the decision of Situbondo No. PA. 0371 / Pdt.G / 2017 / PA.Sit in outline, the procedure of the proceedings and decisions have fulfilled the requirements as regulated in the legislation.